2014
DOI: 10.1021/jf501165z
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic Acid Ameliorates Hepatic Lipid Accumulation and Insulin Resistance in Mice Consuming a High-Fat Diet

Abstract: Effects of asiatic acid (AA) at 10 or 20 mg/kg/day upon hepatic steatosis in mice consuming a high-fat diet (HFD) were examined. AA intake decreased body weight, water intake, feed intake, epididymal fat, and plasma and hepatic triglyceride levels in HFD-treated mice (P < 0.05). HFD enhanced 2.85-fold acetyl coenzyme A carboxylase (ACC1), 3.34-fold fatty acid synthase (FAS), 3.71-fold stearoyl CoA desaturase (SCD)-1, 3.62-fold 3-hydroxy-3-methylglutaryl coenzyme A reductase, 2.91-fold sterol regulatory element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
2
22
0
1
Order By: Relevance
“…Additionally, hepatic biomarkers associated with carbohydrate and lipid metabolism, such as PEPCK, G6P, ACC1, FAS, and SCD‐1 mRNA levels, were significantly increased under the HFD condition. This finding is strongly supported by a previous study . Accordingly, a higher liver TG concentration was found in the SIRT3KO HFD and WT HFD groups, concomitant with increases in the mRNA expression of genes associated with glucose utilization (GLCK, SREBP‐1), fatty acid synthesis (FAS, ACC1, and SCD‐1), and lipid lipogenesis (FAT/CD36) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hepatic biomarkers associated with carbohydrate and lipid metabolism, such as PEPCK, G6P, ACC1, FAS, and SCD‐1 mRNA levels, were significantly increased under the HFD condition. This finding is strongly supported by a previous study . Accordingly, a higher liver TG concentration was found in the SIRT3KO HFD and WT HFD groups, concomitant with increases in the mRNA expression of genes associated with glucose utilization (GLCK, SREBP‐1), fatty acid synthesis (FAS, ACC1, and SCD‐1), and lipid lipogenesis (FAT/CD36) .…”
Section: Discussionmentioning
confidence: 99%
“…Asiatic acid is a triterpenoid component found in Centella asiatica Pakdeechote et al, 2014;Ramachandran et al, 2014), which is an important herb used widely in China and gradually becomes popular in the west (Gohil et al, 2010;Kavitha et al, 2011;Orhan, 2012;Xu et al, 2013;Chen et al, 2014;Yan et al, 2014). Previous studies have demonstrated that asiatic acid could be used for wound healing, various skin conditions, inflammatory, diabetic, hyperlipidemic, and also for anti-depressant, relieving anxiety and improving cognition (Jeong, 2006;Tang et al, 2012;Xu et al, 2012;Zhang et al, 2012;Wei et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since GOAT recognizes fatty acyl-coenzyme (Co)A molecules, such as octanoyl-, hexanoyl-, and decanoyl-CoA [43], we speculated that the carboxyl group in a molecule is an important functional group for this inhibitory effect. Triterpenes, such as asiatic acid, betulinic acid, corosolic acid, glycyrrhetinic acid, oleanolic acid, and ursolic acid have shown antiobesity effects in mice fed a high-fat diet [44][45][46][47][48][49]. Like fatty acids, these triterpenes also have a carboxyl group in their structure, suggesting that they could also suppress octanoylated ghrelin production.…”
Section: Effects Of Triterpenes Contained In E Japonica Leaves On Ghmentioning
confidence: 99%